The effect of physical preparation on the qualities of explosive power and transitional speed, and on the dribbling skills and accuracy of aiming football players in Algeria: أثر التحضير البدني على صفتي القوة الانفجارية والسرعة الانتقالية وعلى مهارتي المراوغة ودقة التصويب عند لاعبي كرة القدم في الجزائر (المجلة العربية للعلوم و نشر الأبحاث, 2017)
The researcher sought to find the relationship between physical preparation and some physical and technical characteristics of football players, where he used the experimental method As a method to study this subject and used physical and technical tests related to football and taken on a sample of nearly14 players. The findings show that physical preparation has an effective and positive effect on transient velocity traits and explosive force. It also has an active role in the development of players technically, in improving the skills of evasion and accuracy of correction